Comparison of structural and spectroscopic properties of Ho3+-doped niobate compounds. (November 2021) - Guene-Girard, S.; Courtois, J.; Dussauze, M.; Heintz, J-M.; Fargues, A.; Roger, J.; Nalin, M.; Cardinal, T.; Jubera, V.
Highlights: Spectroscopic properties of Ho 3+ doped Niobate compounds are described from visible to mid-infrared. A local order/disorder structural environment around the rare earth cation influences the spectral distribution. The Stokes and anti-Stokes energy transfers between Ho 3+ cations depend on the structural properties. Abstract: Ho 3+ -doped YNbO4 and Y3 NbO7 phosphors were synthesised via a co-precipitation synthesis route. Structural characterisation and spectroscopic properties were performed as a function of the Ho 3+ concentration. The Rietveld type-refinement confirms the stabilisation of the pure monoclinic Fergusonite YNbO4 phase at the highest temperatures, but the quadratic phase is stabilised for the lowest temperature, whereas a pure cubic fluorite Y3 NbO7 phase was observed for all of the heat treatments. Raman and infrared spectroscopies were used to compare the cation-oxygen vibrational modes. Emission spectra and up-conversion processes were obtained under excitation at 445 and 975 nm respectively. For a similar Ho 3+ content, the energy transfers observed show differences between the two crystalline compounds that are related to a stronger interaction between the holmium cations in the fluorite host lattice. Graphical abstract: Image, graphical abstract